ANALYSIS OF FACTORS THAT INFLUENCE PRODUCTION OF DRIED ANCHOVY (Stolephorus Sp.) IN PALANG SUB DISTRICT, TUBAN REGENCY - Siti Nur Aisah; Tiwi Nurjannati Utami (Faculty of Fisheries and Marine Science, Brawijaya University, 2016)
The Purposes of this research were to understand the respondent characteristic, to identify and analyse production factors usage in manufacturing of dried anchovy business and analyse influence of production factors of dried anchovy business on production of dried anchovy. These data are analys using quantitative. Define the number of sampel and technique sampling is slovin method and purposive sampling respectively. Data are taken by interview, questionnaire, and documentation by type of data primary and secondary. This research result indicate respondent characteristic based on the age 45-55 years, the education level of senior high school graduate/ equivalent, cost of living for family members about 5-6 people and long-lasting experince about 1-10 years. The independent variable influence dependent variable significantly and those generate production function model Cobb-Douglass Y = -3,276 X10,148 X20,762 X30,340 D10,011 D20,075. Furthermore, the partial independent variable which influence dependent variable are large of area, financial capital, and employees. This research is able to give some suggestions: 1. The owner of the dried anchovy business applicate current technology, like drying machine in production process. 2. The government should give financial capital to improve anchovy production 3. The university is capable of supporting technology like anchovy drying machine. Keywords: Anchovy, Production, Multiple Linear Regression.